Activated carbon from Water Hyacinth as electrocatalyst for oxygen reduction reaction in an alkaline fuel cell. (26th July 2021) - Morales S, L.; Baas-López, J.M.; Barbosa, Romeli; Pacheco, D.; Escobar, B.
Abstract: Water Hyacinth is an invasive aquatic plant with an excellent carbon source with heteroatoms. Activated carbon is a viable choice as an electrocatalyst for fuel cell applications. Based on the plant's leaves, stem, and root, we got activated carbons using KOH at 730 °C with N2 . The samples, named WH_LA730, WH _SA730, and WH_RA730, were examined as electrocatalysts for oxygen reduction reaction in 0.5 M KOH. The high surface area and nitrogen content in the activated carbon provided a good electrochemical activity. The potential reaction for WH_SA730 was at 0.9 V and 0.85 V for WH_RA730. Both samples showed a promising activated carbon for the alkaline fuel cell compared to WH_LA730. Highlights: Carbon materials were prepared by biomass from "Water Hyacinth.". WH_SA730, WH_RA730, and WH_LA730 were evaluated for ORR in an alkaline medium. The activity toward ORR was favored by high surface area and nitrogen content.